Evaluation of the Effectiveness of Soil Nailing Configurations on Slope Stability as an Alternative for Slope Reinforcement in Deep Excavations Case Study of the Rengat–Pekanbaru Toll Road, Pekanbaru Ring Road Section, STA 205+600 - Rully Finaliyah Santoso; Trihanyndio Rendy Satrya; Ria Asih Aryani Soemitro (Green Publisher Indonesia, 2026)
This study evaluated the effectiveness of soil nailing configurations for slope stability as an alternative slope reinforcement method in deep excavations along the Rengat–Pekanbaru Toll Road, Pekanbaru Ring Road Section, Sta 205+600. Limited right-of-way (ROW) conditions required the construction of steeper slopes, necessitating a reinforcement system to maintain slope stability. The analysis was conducted using geotechnical investigation data, including laboratory test results, borehole data, and project-specific geotechnical parameters. The evaluated variations included soil nail length and installation angle, with assessments performed for global stability and internal stability under long-term service conditions (static conditions) and earthquake loading conditions (pseudostatic conditions). The results showed that increasing soil nail length improved the factor of safety (FS) values for both global and internal stability. The highest global stability FS value was achieved with a 19 m soil nail length, while internal stability against pullout resistance increased as soil nail length increased and the installation angle became steeper. Under pseudostatic conditions, soil nailing reinforcement did not provide a significant improvement in global stability for clay soils; however, it continued to enhance internal stability. Based on technical evaluation and cost-efficiency considerations, the 15 m soil nail length with a 30° installation angle was identified as the most effective configuration, as it provided an optimal improvement in safety factors while maintaining more economical construction costs.